(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: This report evaluates the treatment outcomes of intertrochanteric femur fractures using proximal femoral nail antirotation generation II in Vietnamese patients. Methods: A total of 35 patients, including 9 males and 26 females, aged 46-85 years, with intertrochanteric femur fractures, were treated with proximal femoral nail antirotation fixation at Ho Chi Minh city Hospital for Orthopedic and Trauma, from June 2021 to June 2023. Research objects and methods: According to the AO classification system, 20% of fractures were type A1, 57.14% were type A2, and 22.96% were type A3. At the 6-month follow-up, 34 out of 35 patients demonstrated radiographic bone union. Among them, 77.14% had no limb shortening, 7 patients had a shortening of less than 1.5 cm, and 1 patient had a shortening of 2.5 cm. The average neck-shaft angle was 126.3 ± 5.6 degrees. All proximal screws were properly positioned within the femoral head-neck complex, with no cases of screw migration or perforation. According to the Harris Hip Score, 14.3% of patients had poor hip function, 20% had moderate function, and 65.7% had good to excellent function. Complications included 1 case of surgical site infection, 1 case of osteomyelitis, 1 case of pneumonia, and 2 cases of malunion. Conclusion: The second-generation proximal femoral nail antirotation is well-suited to the anatomical structure of the proximal femur in Vietnamese patients, demonstrating favorable treatment outcomes, a high rate of bone union, and a low incidence of severe complications.